Aerodynamic Devices to Reduce/Suppress Vortex Induced Vibrations on a Wind Turbine Tower: A Review. Issue 3 (1st May 2022) - Krishnappa, Likith; Sander, Aljoscha; Thoben, Klaus-Dieter
Abstract: The flow of air over a cylinder at sufficiently high Reynolds number ( Re ) leads to the formation of vortices. The vortices formed undergoes the process of shedding, exerting lift and drag forces onto the cylinder causing the cylinder to oscillate. These oscillations are termed as Vortex Induced Vibrations (VIV). VIV's can induce very high fatigue loads onto the structure, leading to its failure. Hence, the suppression/mitigation of these VIV's is of utmost importance in practical situations. Vortex suppression techniques such as active, passive or compound techniques can be used for the same. This paper focuses on providing a brief overview on the available passive techniques with particular interest in the flow modification, flow separation control devices and their implementation on a wind turbine tower. From this study, it was observed that most of the experimental research related to the testing of the flow modification devices were carried out in a flow channel with water as the flow medium. Therefore, their effectiveness on a wind turbine tower is questionable. However, flow separation control devices were tested in air but these devices have been tested at different Re and therefore their effectiveness cannot be comprehensively compared. The paper concludes by giving a brief overview of the work that will be carried out in the future to tackle this particular problem.